Chasser le naturel : le préjugé métaphysique de Lolita - Antoine Traisnel (Sillages Critiques)
This study pursues the motif of the hunt in Lolita in order to examine what type of relationship the novel entertains with the “real,” when the “real” appears in the guise of one of its most radical forms of alterity: nature. Abundantly metaphorized by the countless figures of animals that populate the text, nature is ubiquitous, and yet Vladimir Nabokov persists in defining literature as that which is born of a non-relationship with nature. This article argues that literature for Nabokov engages reality with a skeptic’s eye, going so far as to posit the absolute sovereignty of the former. Thus literature (and Lolita in particular) chases nature—simultaneously chasing it away and chasing it down in order to master it.